Genetic potential of selected sweet corn inbred lines and analysis of their combining ability assisted by microsatellite DNA markers - Kashiani, Pedram (2012)
A study was conducted to evaluate the potential of sweet corn inbred lines developed from different source populations, to determine genetic diversity among those inbred lines based on agronomic performance and microsatellite DNA markers, to identify major heterotic groups among the inbred lines for selection of potential parents for hybrid production, and to evaluate combining abilities among selected parental inbred lines in a diallel cross. Performance and heterosis of the single-cross hybrids were evaluated at two different locations, Serdang and Sepang. Genetic distances among the inbred lines revealed by the microsatellite markers were used to predict hybrid performance. Thirteen selected sweet corn inbred lines adapted to the tropical environment were evaluated for their performance. Significant variations in agronomic performance were revealed by the inbred lines evaluated, indicating the presence of high genetic diversity among them for potential utilization towards production of hybrid varieties. Among the inbred lines, the highest husked fresh ear yield was obtained from TSN-S8 with value of 6549 kg ha-1, but this was not significantly higher than those obtained from TSK-S8,BAK-S8 and MAN-S8 (6483, 6402 and 5798 kg ha-1, respectively). Microsatellite markers exhibited high Shannon’s information index (I), Nei’s expected heterozygosity (Nei’s), and polymorphic information content (PIC), with mean values of 1.053, 0.586 and 0.582 respectively, indicating their appropriateness in detecting genetic variability among the inbred lines. Molecular analysis of variance showed that 92.88% of the total variation occurred among the inbred lines while only 7.11% occurred within the inbred lines. Shannon’s information index and Nei’s gene diversity coefficient showed that Chromosome 10 was the most informative chromosome (I = 1.311 and Nei’s = 0.703), while Chromosome 2 had the least variation among the chromosomes evaluated (I = 0.762 and Nei’s = 0.456). Chromosome 4 was found to possess the highest number of pairs of alleles in linkage disequilibrium (122 pairs), while Chromosome 6 was found to have only six pairs of alleles in linkage disequilibrium. The inbred lines were assigned into five main heterotic groups based on their agronomic and molecular characteristics. MAS-S8, DFS-S8, TSN-S8, TZF-S8 and SBY-S8 each from a different heterotic group were selected as parental inbred lines for a diallel cross. From results of evaluations on the hybrids, Hybrids H2 and H1 were found to have the highest fresh ear yield in Serdang, with mean values of 15475 and 15124 kg ha-1, respectively, while Hybrids H3 and H1 revealed the highest fresh ear yield in Sepang (15143 and 14998 kg ha-1, respectively). There was no significant difference in fresh ear yields between these hybrids and that of the control variety (Hybrid 968), indicating that fresh ear yield of these hybrids could be comparable to those of the commercial hybrids available in the market. Among the traits measured, husked fresh ear yield exhibited the highest mid- and high-parent heterosis at the two locations of study. In general, Hybrids H1, H2 and H3 had high and consistent estimates of mid- and high-parent heterosis for all traits measured, indicating that they accumulated favorable genes possessed by their parental inbred lines. Combining ability analysis revealed presence of significant additive and non-additive gene actions in control of the traits measured. However, additive gene effects were found to be relatively more important in the control of yield and yield components in the hybrids, based on greater GCA mean squares than SCA mean squares that they possessed. DFS-S8, with the highest positive and significant GCA for husked fresh ear yield in Serdang, Sepang and the two locations combined (3091.54, 2370.98 and 2731.26 respectively), was identified as the best general combiner among the parental inbred lines for high yield and yield components in its crosses. DFS-S8 X MAS-S8 (H3), DFS-S8 X SBY-S8 (H4), TFZ-S8 X TSN-S8 (H5) and TFZ-S8 X SBY-S8 (H7) were the best cross combinations, with favorable positive SCA estimates for yield and yield related traits at each location and locations combined. The Wr-Vr graphical analysis showed that non-additive gene effects that controlled the traits were overdominance for all traits measured. The overdominance mode of gene action was also revealed through greater estimates of variation due to dominance effects of genes (H1 and H2) than additive effect (D), and estimates of average degree of dominance higher than unity. The high true-sense heritability estimates (more than 50%) revealed the presence of high proportion of genetic variability in the whole phenotypic variability, while the presence of high broad-sense heritability estimates (more than 80%) indicate a close correspondence between the genotype and the phenotype, due to a relatively smaller contribution of the environment to the phenotype. The narrow-sense heritability estimates revealed were however generally lower than the broad-sense heritability estimates, indicating the preponderance of non-additive gene actions in the inheritance of all traits measured. Significant positive associations were obtained between genetic similarities of the parental inbred lines estimated based on microsatellite markers with more than 30% polymorphic bands and SCA estimates for number of ears per hectare, husked and dehusked ear weights, TSS, husked and dehusked ear diameter and number of kernels per row. This indicates the effectiveness of molecular markers for prediction of hybrid performance from those tropical sweet corn inbred lines. In conclusion, among the 10 tropical hybrids produced, Hybrids H1, H2 and H3 exhibited high yield performance and high magnitude of yield components at each location and the two locations combined. It is thus suggested that these promising hybrids be further tested in large scale multi-locational trials before their release as new tropical sweet corn hybrid varieties in Malaysia.